Effect of malonaldehyde on the gelation properties of myofibrillar proteins of sea salmon - Tironi, Valeria Anahi (2003)
Myofibrillar proteins incubated with malonaldehyde (27°C, t = 0 to 8 h) were used to prepare gels by thermal treatment (80°C, 45 min). Malonaldehyde did not produce significant modifications (P > 0.05) in the storage modulus (G') and complex viscosity (η*) except for t = 0. Texture analysis showed a significant increase (P < 0.05) in elasticity and cohesiveness with hardness approximately constant. Relaxation test presented a marked increase in the elasticity index. A significant decrease (P < 0.05) in water holding capacity (WHC) was recorded. Ultrastructure showed a different network with the appearance of big filaments. Electrophoretic patterns of protein dispersions remainder after gel formation showed a decrease of 81, 53, 25 to 50, and 20 kDa polypeptides.